Service Quality Affecting to Customer’S Satisfaction toward the Artificial Football Turf (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The service quality is the thing that all customers expect to gain the best product and the best service, so the customer’ssatisfaction depend on how the service quality are. It is therefore the problem of the artificial football turf spreading, but manyof them are still lacking of the good service quality which will affect the customer’s satisfaction in the issue of repeating usefrom those customers. Objective: To study the service quality affecting the customer’s satisfaction toward the artificial footballturf. Methods: This study employed a quantitative research design which the phase of data collection by the questionnaire with260 participants by non-probability sampling with the accidental method, and analyzed with the descriptive statistic andcorrelation research method. Results: The service quality which were comprised of 1) Tangible, 2) Reliability, 3) Responsive, 4)Assurance, and 5) Empathy have the correlation with the customer’s satisfaction toward the artificial football turf (r = 0.820 –0.901) with statistically significant at the 0.05 level (P-value = 0.00).